2010
DOI: 10.1111/j.1464-5491.2009.02875.x
|View full text |Cite
|
Sign up to set email alerts
|

Biofeedback for foot offloading in diabetic patients with peripheral neuropathy

Abstract: Terminal augmented feedback training may positively affect motor learning in diabetic patients with peripheral neuropathy and could possibly lead to suitable foot offloading. Additional research is needed to confirm the maintenance of offloading in the long term.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
79
0
8

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(88 citation statements)
references
References 20 publications
1
79
0
8
Order By: Relevance
“…Previous studies do not describe the foot rollover changes after such a specific set of exercises for foot and ankle [24-27]. Usually, attention is mostly given to PP and PTI reduction as a target to reduce the risk of ulceration, but these variables should be analyzed together with several other risk factors [4,5,36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies do not describe the foot rollover changes after such a specific set of exercises for foot and ankle [24-27]. Usually, attention is mostly given to PP and PTI reduction as a target to reduce the risk of ulceration, but these variables should be analyzed together with several other risk factors [4,5,36].…”
Section: Discussionmentioning
confidence: 99%
“…Few authors have described the subtle, positive effects of foot and ankle exercises in this population, although some studies were not randomized controlled trials [24,25], and others reported on quite short interventions and follow-up periods [26,27]. Therefore, there are still not enough data for conclusions to be arrived at regarding the effectiveness of such interventions.…”
Section: Introductionmentioning
confidence: 99%
“…In this idea, researches evaluating the effect of ''psychological interventions'' exclude the ''education'' and compare different psychological interventions to control groups, these latter being a melting pot that can contain ''waiting list'' as well as ''education'' [8]! For us, a complex intervention aiming to the patient's learning includes all known ways of proven, effective education processes, including providing information, psychological interventions such as Cognitive and Behavioral Therapies (CBT), a process known as behavioral education in education science, and many others such as bio-feedback [42,43].…”
Section: Efficacy Underestimatedmentioning
confidence: 99%
“…Presence of sensitivity dysfunction is the main symptom of diabetic polyneuropathy-loss of peripheral nerve fiber function-considered the most common predictor of diabetic foot ulceration and symptom associated with a lack of metabolic control of the patient [29]. This result indicates that HbA 1c could also be investigated as a likely marker of risk of diabetic neuropathy-Necessary condition for the appearance of ulcers in Type 2 DM patients.…”
Section: Discussionmentioning
confidence: 99%